Impairment mechanism of nasal mucosa after radiotherapy for nasopharyngeal carcinoma - Fang, Caishan; Zhong, Yu; Chen, Tengyu; Li, Dan; Li, Chunqiao; Qi, Xiangjun; Zhu, Junxia; Wang, Ruizhi; Zhu, Jinxiang; Wang, Shunlan; Ruan, Yan; Zhou, Min (Frontiers in Oncology, 2022)
The nasal mucosa, which performs the crucial functions of filtering, humidifying and temperature regulation, is one of the most vulnerable areas of nasopharyngeal carcinoma (NPC) patients after radiotherapy (RT). Following RT, NPC patients experience a series of pathological changes in the nasal mucosa, ultimately leading to physiological dysfunction of the nasal epithelium. This article systematically reviews the clinical and pathological manifestations of RT-related nasal damage in NPC patients and summarizes the potential mechanism of damage to the human nasal epithelium by RT. Finally, we outline the current mechanistic models of nasal epithelial alterations after RT in NPC patients and provide additional information to extend the in-depth study on the impairment mechanisms of the nasal mucosa resulting from RT. We also describe the relationship between structural and functional alterations in the nasal mucosa after RT to help mitigate and treat this damage and provide insights informing future clinical and fundamental investigations.